The use of aggregate complaints data as an indicator of cumulative social impacts of mining: A case study from the Hunter valley, NSW, Australia - Moran, Chris; Brereton, D. (Pergamon Press, 2013)
Generally speaking, there is a greater amount of quantitative data available to measure and model the cumulative environmental or economic impacts of mining than the social impacts. In part, this is because social impacts are often inherently more difficult to quantify, but historically there have also been fewer regulatory drivers for companies or state agencies to invest in collecting such data. Regulators in some jurisdictions are now starting to require resource companies to report on aspects of their social performance, but companies and regulators are still struggling to identify appropriate metrics, particularly in regards to cumulative impacts. This paper describes an innovative quantitative approach to tracking how communities experience and respond to increased mining activity, using data from the complaints registers maintained by mines located in the Upper Hunter Valley in New South Wales, Australia. In this study, complaints lodged with five separate mines adjacent to the township of Muswellbrook over several years were aggregated and trends analysed. The aggregated set showed that complaint frequency increased with the increase in mining activity but then decreased as individual complaints were addressed. However, when complaints from near-neighbours were removed, it emerged that the proportion of complaints that came from the town itself steadily increased over time. Further analysis indicated that this increase was closely associated with the amount of mine-disturbed land that could be seen from the town over time, as measured using a combination of remotely sensed data and a digital elevation model. This is persuasive evidence of a cumulative social impact that is more than just the sum of the local impacts of individual mines. © 2013.